Imagining the monstrous other: An introduction to the research on the medicalized undead - Mandić Marina (Glasnik Etnografskog Instituta SANU)
Monsters are liminal subjects, whose ambivalent position challenges culturally established distinctions between the normal and abnormal, the ordered and disordered, and the healthy and unhealthy. They blur the lines between self and other, the familiar and the unfamiliar, and the “us” versus “them.” The indeterminacy of these categories embodies itself in what we term „human monsters” — Individuals transformed into monsters after death. These undead figures display the terrifying consequences of their transformation, primarily through their uncanny appearance and identity characteristics. This paper serves as an introduction to various perspectives on monstrous Others and the medicalization of the undead (mainly zombies). It aims to formulate initial hypotheses for researching the impacts of disease, death, and monstrous transformation, including bodily, identity, and cognitive characteristics that determine and redefine our understanding of monstrosity and humanity.